Canine primary cardiac hemangiosarcoma of right atrium in a Rottweiler of eight years old - Salinas C., Eben (2017)
Haemangiosarcoma is a malignant tumour of vascular origin and it is the most frequent of cardiac tumours in dogs. It is presented the case of a 8-year old Rottweiler dog with dyspnea, pale mucous and intolerance to exercise. Cardiac sounds were slightly perceptible with decreased femoral pulse. Lab tests showed thrombocytopenia, and acute kidney failure. Radiographic and echography tests were carried out identifying only pericardial effusion and cardiac obstruction. Pericardiocentesis was performed which cytology study was compatible with bloodstained serum exudate. A computerized axial tomography in thorax only detected enlargement of the right atrium. A right lateral thoracotomy was performed, identifying a neoplastic mass in the right atrium and several metastatic nodules in lungs and pericardium. The histopathological study diagnosed a primary cardiac hemangiosarcoma in the right atrium of cavernous type.